Medial swivel type dislocation of the talonavicular joint with associated cuboid fracture: a case report - Astawa, Ni Made Puspa Dewi; Aryana, I. Gusti Ngurah Wien; Maharjana, Made Agus; Simanjuntak, Herryanto Agustriadi; Stanu, Gusti Ngurah Putra; Purvance, Ivander; Putra, I. Gede Mahardika (International Journal of Research in Medical Sciences, 2020)
Medial Swivel-type dislocation are dislocation of talonavicular joint (TNJ) medially and the calcaneus swivels under the talus, with the calcaneocuboid joint intact. This is a rare injury due to the strong network of ligament and tendinous structures. An 11-year-old girl presented after 1 week of injury to the left foot. She had pain, swelling on the mid-foot and inability to weight bearing. X-ray and computerized tomography (CT) scan showed medial dislocation of TNJ, with fracture of cuboid body. A closed reduction was attempted but it failed. Patient then underwent open reduction with K-wire fixation and immobilization by below knee cast for 3 weeks. After K-wire removal, the foot was stable with near normal ankle and sub-talar joint range of motion and patient started to partial weight bearing Midtarsal dislocations of the foot are rare injuries. In this case dislocation is resulted from high-energy medial forces to the forefoot. The associated cuboid fracture possibly as a result of tensile forces through the lateral structure of midfoot with adduction. ‘Swivel dislocation’ in which the TNJ dislocates, usually medially, and the calcaneus swivels under the talus, with the calcaneocuboid joint intact. A careful assessment of initial radiograph and CT scan should be done to determine type of dislocation and associated fracture. An open reduction K-wire fixation bring a stable reduction. Talonavicular dislocations are rare injuries, occur as a result of high-energy trauma. A stable reduction and good outcome are anticipated.